Vertical coordination mechanisms and farm performance amongst smallholder rice farmers in northern Ghana - Awal Abdul-Rahaman; Awudu Abdulai (Agribusiness, 2019)
Despite the fact that contracting facilitates farmer participation in agrifood value chains, evidence on farmers' participation in different forms of contracts and the impact on farm performance is still limited. This study examines the determinants and impacts of vertical coordination mechanism-spot market transactions, written, and verbal contract-on-farm performance of rice farmers in northern Ghana, using a multinomial BFG model to account for selectivity bias. The findings indicate that vertical coordination participation decision is significantly influenced by age, access to credit, labor, association membership, and sales to institutional buyers. The empirical results also reveal significant gains in farm performance outcomes from participating in written and verbal contracts, relative to spot market transactions.
Keywords: 630; C34; C35; D23; Q12; Q13